Incorporating progress bar and danmaku in MOOCs: effect on learning motivation through psychological distance - Liang, Diqiao (Nanyang Technological University, 2025)
Massive Open Online Courses (MOOCs) enable distance learning, free choice, open access, and unlimited enrolment, but face challenges with students' learning motivation and completion rates. While previous research has designed and evaluated gamification elements in online learning environments to address such challenges, there are understudied elements, such as a progress bar and an interactive commentary system, named danmaku, that can have a synergetic impact on learning motivation, satisfaction, and outcomes. This thesis applies progress bars and danmaku in MOOCs and introduces Construal Level Theory (CLT) as the theoretical framework, in which hypothetical distance to MOOC completion and social distance to MOOC peers are mediators. An experiment (N = 153) with a 2 (progress bar presence) x 2 (danmaku presence) mixed design was conducted. Results show that while hypothetical distance is positively related to learning variables, the effects of the progress bar and danmaku are not statistically significant. Practical and theoretical implications and suggestions for future studies are discussed.